Hormonal Profile and Fertility Response to Modified Ovsynch Protocol in Repeat Breeding Crossbred Cows with Prolonged Estrus - Patel, Dhaval N.; Nakhashi, Haresh C.; Chauhan, Prakash M.; Sutaria, Tarun V.; Chaudhari, Ashwin I.; Chaudhari, Ravji K.; Suthar, Babulal N. (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
The present study was conducted to determine the hormonal profile and fertility response in prolonged estrus affected repeat breeder crossbred cows by using modified ovsynch protocol. Total 20 crossbred cows, not conceiving even after more than four services were selected from the semi-arid area of Banaskantha district in Gujarat. They were divided into two equal groups: Group-I (n=10) - cows with prolonged estrus period (>28 hrs) and Group-II (n = 10) - cows with normal estrus period (18 to 28 hrs). The animals of both groups were treated with modified ovsynch protocol using double dose of GnRH (@ 20 μg) starting from 5th day of estrous cycle. The blood was collected on day 0, 7th, 9th and 25th (15th day post-FTAI) of the treatment for determination of plasma progesterone and estradiol hormones. The conception rates in group I and II were 60 and 70%, respectively. The cows with prolonged estrus had non-significantly higher mean plasma progesterone (3.51 ± 0.45 vs 2.97 ± 0.38 ng/ml) and lower estradiol (44.36 ± 1.74 vs 54.56 ± 2.49 pg/ml) as compared to normal estrus cows on day 0 of protocol. The progesterone levels were significantly (p <0.05) higher on day 7th (day of PG injection) and 9th (day of second GnRH injection) of protocol in prolonged estrus cows than normal estrus group. The plasma estradiol concentration was significantly (p <0.05) lower at all the periods in prolonged estrus cows than those of normal estrus group, except on 25th day. In repeat breeding cows with prolonged estrus, the plasma progesterone concentration was significantly higher on day 25 (day 15 post AI) of treatment in conceived as compared to non-conceived cows, whereas in normal estrus cows, there was no significant difference. While, estradiol concentration was significantly lower in conceived than non-conceived cows in both the groups.